Influence of well doping on the performance of UTBB MOSFETs *Project supported by the National Key R&D Plan (No. 2016YFA0202101). (December 2018) - Ren, Yuqi; Huang, Shizhen; Shen, Lei; Liu, Xiaoyan; Du, Gang
Abstract: In this work, the impact of well doping and corresponding body bias on UTBB MOSFETs is investigated. The ability of threshold voltage adjustment is evaluated. The results indicate that well doping can change the threshold voltage both of the N and P channel UTBB MOSFETs. The maximum amplitude for a typical 26 nm gate length device is about 100 mV, and these correspond to the cases of devices with an inverse type of high concentration dopant. The body bias adjusts the threshold voltage at a rate of 100–140 mV/V for the UTBB MOSFETs with a well. By optimizing well doping and body biasing, multi-threshold-voltage UTBB MOSFETs can be designed and optimized for lower power application.